Rho-kinase Is Involved in the Sustained Phosphorylation of Myosin and the Irreversible Platelet Aggregation Induced by PAR1 Activating Peptide - Missy, K.; Plantavid, M.; Pacaud, P.; Viala, C.; Chap, H.; Payrastre, B. (Thrombosis and Haemostasis, 2001)
We have addressed the role of Rho-kinase in the different steps of thrombin receptor agonist peptide (TRAP) -induced platelet activation. Interestingly, under physiological conditions, incubation of platelets with increasing concentrations of the specific Rho-kinase inhibitor Y-27632 resulted in a dose-dependent reversion of the aggregation induced by 10 μM TRAP, without affecting serotonin secretion. Addition of Y-27632 after three minutes of TRAP stimulation, when the maximal aggregation was reached, resulted in a rapid disaggregation of platelets. Accordingly, the early peak of myosin light chain (MLC) phosphorylation induced by TRAP was not affected by Y-27632 but its sustained phosphorylation, observed during the irreversible phase of aggregation, was dependent of Rho-kinase activity. The rapid decrease in MLC phosphorylation upon Y-27632 treatment correlated well with the specific disappearance of myosin heavy chain from the cytoskeleton and preceded platelet disaggregation. Finally, we provide evidence that secreted ADP, known to play a key role in TRAP-induced irreversible phase of aggregation, was involved in the sustained MLC phosphorylation through Rho-kinase and could be replaced by epinephrine.
Keywords: Rho-kinase; irreversible platelet aggregation; myosin; TRAP